Go for it ! : - Nunan, David (Thomson, 2005)
Perfect for summer school, before/after school intervention, community-based English tutoring programs, and dual-language instruction programs, GO FOR IT! develops students' school survival vocabulary and language skills through its lively pace, engaging topics, and variety of activities.